2016
DOI: 10.1177/1073858416673327
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Metabonomics on the Neurobiology of Stroke

Abstract: The application of metabonomic science to interrogate stroke permits the study of metabolite entities, small enough to cross the blood-brain barrier, that provide insight into neuronal dysfunction, and may serve as reservoirs of biomarker discovery. This systematic review examines the applicability of metabolic profiling in ischemic stroke research. Six human studies utilizing metabolic profiling to analyze biofluids from ischemic stroke patients have been included, employing H-NMR and/or mass spectrometry to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 37 publications
0
24
0
5
Order By: Relevance
“…Urine, on the other hand, is largely considered water, While the trace amounts of metabolites has a high diagnostic value of biological fluid and it can be used to search for biomarkers of central nervous system diseases. [ 13 , 14 ] So far, many researchers have used metabolomics successful identification of potential diagnostic biomarkers neuropsychiatric disorders, such as bipolar disorder and schizophrenia Autism. [ 15 , 16 ] Studies also found that differences in urine metabolites can be used to Distinguish between healthy and depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Urine, on the other hand, is largely considered water, While the trace amounts of metabolites has a high diagnostic value of biological fluid and it can be used to search for biomarkers of central nervous system diseases. [ 13 , 14 ] So far, many researchers have used metabolomics successful identification of potential diagnostic biomarkers neuropsychiatric disorders, such as bipolar disorder and schizophrenia Autism. [ 15 , 16 ] Studies also found that differences in urine metabolites can be used to Distinguish between healthy and depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Use of such medications as statins was not considered by investigators. Statins may both produce signals in the plasma/serum and also induce a physiological response that may be detected in the plasma metabolome [85]. Although some studies elaborated on the timing of bodily fluid collection in relation to acute stroke, none of them accounted for the size of ischemic stroke and its possible effect on metabolome.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…It is suggested that NMR metabolomics can be incorporated as a routine survey in large biobanks, which is beneficial both from the inexpensiveness and reproducibility [33, 34]. Successful examples include NMR metabolic profiling of cardiovascular events [3538] and ischemic stroke [39]. Stegemann et al found three lipid species (triacylglycerols, cholesterol esters, and phosphatidylethanolamines) on top of traditional risk factors could improve risk discrimination and classification for cardiovascular disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…Wurtz et al reported tyrosine and glutamine levels were cross-sectionally associated with carotid intima media thickness and the presence of angiographically ascertained CAD in independent populations [36]. Review article by Qureshi et al demonstrated certain metabolic pathways may be related to the pathological processes of stroke, particularly including branched chain amino acid, homocysteine, folate, anaerobic, and lipid metabolism [39]. Levels of plasma branched-chain amino acid, measured by NMR, were found elevated in type 2 diabetes and could be associated with carotid intima media thickness, a proxy of subclinical atherosclerosis [40].…”
Section: Discussionmentioning
confidence: 99%